A coupled framework of variational asymptotic method based homogenization technique and Monte Carlo approach for the uncertainty and sensitivity analysis of unidirectional composites. (1st May 2021) - Pitchai, Pandi; Jha, Niraj Kumar; Nair, Rajeev G.; Guruprasad, P.J.
Abstract: This article describes a computational framework, based on the variational asymptotic method unit cell homogenization technique coupled with the Monte Carlo method, for carrying out uncertainty and sensitivity analysis of the effective properties of fiber reinforced plastic composites. As an application, univariate and multivariate analysis have been undertaken to investigate the influence of the constituent material properties on the effective properties of the FRP composites. Both bivariate and global sensitivity analysis results are presented to highlight the contribution of the uncertainty in the properties of the constituent materials on the uncertainty in the effective properties. Model predictions are validated by comparing the results with data reported in literature.